The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/mcs.a003772
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA dynamics using patient-customized assays are associated with outcome in neoadjuvantly treated breast cancer

Abstract: Pathological complete response (pCR) is an accurate predictor of good outcome following neoadjuvant chemotherapy (NAC) for locally advanced breast cancer. The presence of circulating-tumor DNA (ctDNA) has recently been reported to be strongly predictive of poor outcome in similar patient groups. We monitored ctDNA levels from 10 women undergoing NAC for locally advanced breast cancer using a patient-specific, hybrid-capture sequencing technique sensitive to the level of one altered allele in 10,000. Plasma was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Our results are similar to those of McDonald et al, who developed a multiplex targeted digital sequencing approach for the detection of very low abundance ctDNA. At a timepoint similar to our T4, they reported that ctDNA was detected in 12 of 13 patients without pCR and in 5 of 9 patients with pCR 19 . Our analogous numbers are 13 of 17 without pCR and 2 of 7 with pCR.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results are similar to those of McDonald et al, who developed a multiplex targeted digital sequencing approach for the detection of very low abundance ctDNA. At a timepoint similar to our T4, they reported that ctDNA was detected in 12 of 13 patients without pCR and in 5 of 9 patients with pCR 19 . Our analogous numbers are 13 of 17 without pCR and 2 of 7 with pCR.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, the early decrease in ctDNA levels appears to be mostly the result of the effect of chemotherapy on the primary tumor's ability to generate ctDNA, and not on initial tumor response. Butler et al 19 , who showed similar results, suggest that chemotherapy may selectively kill actively dividing cells, which are the majority secretors of ctDNA. Nevertheless, those patients whose tumors eventually showed complete pathological response were less likely to have detectable ctDNA at this early stage of neoadjuvant treatment (33% vs 83%).…”
Section: Discussionmentioning
confidence: 84%
“…2 Line graphs depicting the VAF of mutations (labelled on each graph) detected in patients 1 to 5 (a-e, respectively) at baseline, 3 days and 7 days mid-treatment exhibited a transient rise prior to the eventual decrease (3/14 [23] and 2 /10 [24]). In addition, transient rises in ctDNA have been observed following systemic therapy, such as immunotherapy in melanoma [39], neoadjuvant combined cytotoxic/biologic combination therapy in breast carcinoma [40] and tyrosine kinase inhibition in EGFR-mutant NSCLC [41]. This pilot study demonstrates the feasibility of applying ctDNA-optimised NGS protocols through specified time-points in a small, homogenous cohort of patients treated with modern radiotherapy planning for locally advanced NSCLC.…”
Section: Discussionmentioning
confidence: 87%
“…63 A liquid biopsy may be able to reveal tumour information prior to clinical progression. 133,134 However, the tumour morphological features and the microenvironment are more readily available in the tissue biopsy. Therefore, a liquid biopsy aims to provide additional and complementary data to improve upon the diagnosis and follow-up of GBM patients.…”
Section: Discussionmentioning
confidence: 99%